Proposed sets of critical exponents for randomly branched polymers, using a known string theory model. (2nd June 2016) - March, N.H.; Moreno, A.J.
Abstract : The critical exponent ν for randomly branched polymers with dimensionality d equal to 3, is known exactly as 1/2. Here, we invoke an already available string theory model to predict the remaining static critical exponents. Utilizing results of Hsu et al. (Comput Phys Commun. 2005;169:114–116), results are added for d = 8. Experiment plus simulation would now be important to confirm, or if necessary to refine, the proposed values.